Hematological changes in patients affected by COVID-19 (Research, Society and Development, 2021)
This work focused on evaluating the main changes caused in the blood system in patients with COVID-19. This is a systematic literature review based on searches in the PubMed and Science Direct databases, using specific descriptors. Only studies in their full versions, with no language restrictions and published in the time frame from December 2019 to November 2020, were included. SARS-CoV-2 may be related to several alterations in various organs and systems, including the hematopoietic system. The various hematological alterations caused by the infection resulting from the new coronavirus are of paramount importance given the current health problem, considering that such alterations may be directly related to the poor prognosis and even the death of many patients. The SARS-CoV-2 is the seventh in the family to be described as being associated with the disease in humans, having great ease of interpersonal transmission and, therefore, it can spread quickly. As for symptoms, COVID-19 is characterized as an infection with a broad symptomatological spectrum, which can range from a completely asymptomatic condition to severe clinical conditions with systemic symptoms and in multiple organs. There are several changes in hematopoietic tissue, with emphasis on disturbances in the coagulation cascade, such as the incidence of thromboembolic events, increase in Prothrombin Time and Activated Partial Thromboplastin Time, followed by a decreased platelet count, exacerbated increase in D-dimer, in addition to the low clotting activity of fibrinogen.